Kemampuan Literasi Sains Kimia dan Hubungannya dengan Prestasi Belajar Murid Kelas X pada Materi Hukum – Hukum Dasar Kimia - Diannisa Mahiru Suryani; Abdullah Abdullah; Rasmiwetti Rasmiwetti (Lembaga Yasin AlSys, 2026)
Scientific literacy is an important competence in chemistry learning because it supports students in understanding concepts, applying scientific knowledge, and interpreting phenomena rationally. However, the relationship between chemical scientific literacy and students’ learning achievement on the topic of the Basic Laws of Chemistry still needs to be examined empirically. This study aims to describe chemical scientific literacy, students’ learning achievement, and analyze the relationship between chemical scientific literacy and learning achievement on the topic of the Basic Laws of Chemistry at SMAN 5 Pekanbaru. This study used a correlational quantitative approach with a survey method. The research sample consisted of 98 Grade XI students selected using purposive sampling. Data were collected through a chemical scientific literacy test based on PISA scientific literacy dimensions and documentation of learning achievement scores, then analyzed using descriptive statistics and the Spearman Rank correlation test. The results showed that students’ chemical scientific literacy was in the high category, with an average score of 79.63, whereas learning achievement was in the good category, with an average score of 87.57. The correlation test results showed a positive and significant relationship between chemical scientific literacy and students’ learning achievement (r_s = 0.537; p < 0.001). These findings indicate that the higher students’ chemical scientific literacy, the higher the learning achievement attained on the topic of the Basic Laws of Chemistry. The conclusion of this study emphasizes the importance of strengthening scientific literacy in chemistry learning to support conceptual understanding and improve learning achievement. The implications of this study provide practical contributions for chemistry teachers in designing learning oriented toward the development of scientific literacy and the achievement of more optimal learning outcomes.